Pengembangan Aplikasi Pengelolaan Usaha Laundry berbasis Website - Andicha Eka Prastya; Nurudin Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
In the current technological era, more and more human activities are switching to using technology because it is able to improve performance and is more effective and efficient. The use of technology is not only felt by big business stakeholders, but can also be felt by small businesses in the community, one of which is the laundry business. Laundry businesses are able to reach customers in all walks of life, and most of them are located close to workplaces and also campuses and schools. The number of customers makes business actors have to work extra in order to serve customers well, one of which is at a laundry business located in Malang City. To help the work system in the laundry business, an application that is able to handle all business matters is needed to make it easier in the process. The application used is website-based because it can be accessed for 24 hours and also the application can be opened on all devices, both on smartphones and on computers, making it easier to use. The development is carried out using the Rapid Application Development (RAD) method because this method is able to make application development faster and in accordance with the required needs. This system has 21 functional requirements and has 3 actors in the system. The development is done by implementing the MERN stack, which consists of Mongo DB, Express JS, React JS, and Node JS, and using the MVC (Model, View, Controller) method. The tests carried out apply unit testing, integration testing, and system testing, using black box and white box methods, and get 100% valid results from the tested functionality.